Physical fitness of elementary children through Balinese traditional games based on the tri hita karana philosophy - I Kadek Happy Kardiawan; I Made Sutajaya; I Wayan Suja; Wahjoedi Wahjoedi; I Ketut Iwan Swadesi (Universitas Sriwijaya, 2023)
Physical education, sports, and health (PJOK) is a subject that educates students through physical activity to improve student’s fitness and healthy lifestyles. The physical activity that can be carried out can be traditional games from each region which contain noble cultural values of the region and nation. Traditional Balinese games are games that educate students about the harmonization of life following the philosophy of Tri Hita Karana, namely harmonious relations with fellow human beings, environmental preservation, and devotion to God Almighty